Atomically Sharp Dual Grain Boundaries in 2D WS2 Bilayers. Issue 42 (25th August 2019) - Chen, Jun; Jung, Gang Seob; Ryu, Gyeong Hee; Chang, Ren‐Jie; Zhou, Si; Wen, Yi; Buehler, Markus J.; Warner, Jamie H.
Abstract: It is shown that tilt grain boundaries (GBs) in bilayer 2D crystals of the transition metal dichalcogenide WS2 can be atomically sharp, where top and bottom layer GBs are located within sub‐nanometer distances of each other. This expands the current knowledge of GBs in 2D bilayer crystals, beyond the established large overlapping GB types typically formed in chemical vapor deposition growth, to now include atomically sharp dual bilayer GBs. By using atomic‐resolution annular dark‐field scanning transmission electron microscopy (ADF‐STEM) imaging, different atomic structures in the dual GBs are distinguished considering bilayers with a 3R (AB stacking)/2H (AA′ stacking) interface as well as bilayers with 2H/2H boundaries. An in situ heating holder is used in ADF‐STEM and the GBs are stable to at least 800 °C, with negligible thermally induced reconstructions observed. Normal dislocation cores are seen in one WS2 layer, but the second WS2 layer has different dislocation structures not seen in freestanding monolayers, which have metal‐rich clusters to accommodate the stacking mismatch of the 2H:3R interface. These results reveal the competition between maintaining van der Waals bilayer stacking uniformity and dislocation cores required to stitch tilted bilayer GBs together. Abstract : Long‐range atomically sharp dual tilt grain boundaries are found within bilayer WS2 2D layered crystals grown by chemical vapor deposition. In situ heating experiments within the electron microscope show they are stable to at least 800 °C. The dislocation cores needed for these bilayer interfaces are more complex than monolayer grain boundaries due to competing van der Waals interlayer forces.